A survey of the diversity of human enteric protoctistan parasites and the associated risk factors in urban Zvishavane, Zimbabwe - Patience, Masungo; Dube, Trevor; Makaka, Caston (Science Huβ, 2018)
Community based survey of the diversity of human enteric protoctistan parasites was done on a random sample of 300 individuals in urban Zvishavane, Zimbabwe from December 2007 to May 2008. Stool, fruit, vegetable, water and pest sample specimens were analysed using the following techniques; permanent stains, microscopic analysis and the formol-ether concentration method. Stool specimen analysis showed that 98 individuals (32.67%) of the population were infected with enteric protoctistan parasites. Infestation by Enterocytozoon bieneusi (30.1%), Cryptosporidium parvum (18.4%), Entamoeba histolytica (16.5%), Encephalitozoon intestinalis (14.6%), Cyclospora cayetanensis (12.6%) and Giardia lamblia (7.8%) were noted amongst the residents. The 20-35 age group accounted for half (47.96%) of the infections. Infection frequencies were higher in the high density areas (HDAs) than in the low density areas (LDAs). There were significant differences in infection levels between residents in southern and nothern HDAs (tc = 3.226, p < 0.01). However there were no significant differences in infection loads between southern and northern LDAs (tc = 1.912, p > 0.05). Risk factors included age, host density, pregnancy, infection by HIV or recent surgery. Improving the socio-economic conditions and raising awareness on issues related to intestinal parasitosis would aid in decreasing the infection levels in urban Zvishavane.